Performance Evaluation of Downlink WiMAX System in Vicinity of UWB System - Al-Adwany, Maan A. S. (Iraqi Journal for Electrical and Electronic Engineering, 2011)
In this paper, we evaluate the performance of WiMAX downlink system in vicinity of UWB system. The study is achieved via simulating a scenario of an office building which utilizes from both WiMAX and UWB appliances. From the simulation results, we found that WiMAX system is largely affected by the UWB interference. However, in order to overcome the interference problem and achieve reasonable BER (Bit Error Rate) of 10 -4 , we found that it is very necessary to raise the WiMAX transmitted power in relative to that of UWB interferer. So, the minimum requirements for WiMAX system to overcome UWB interference are stated here in this work.